Numerical Analysis of the Width Design of a Protective Pillar in High-Stress Roadway: A Case Study - FuZhou Qi; ZhanGuo Ma; Ning Li; Bin Li; Zhiliu Wang; WeiXia Ma (Advances in Civil Engineering)
The width design of protective pillars is an important factor affecting the stability of high-stress roadways. In this study, a novel numerical modeling approach was developed to investigate the relationship between protective pillar width and roadway stability. With the 20 m protective pillar width adopted in the field test, large deformation of roadways and serious damage to surrounding rocks occurred. According to the case study at the Wangzhuang coal mine in China, the stress changes and energy density distribution characteristics in protective pillars with various widths were analysed by numerical simulation. The modeling results indicate that, with a 20 m wide protective pillar, the peak vertical stress and energy density in the pillar are 18.5 MPa and 563.7 kJ/m3, respectively. The phenomena of stress concentration and energy accumulation were clearly observed in the simulation results, and the roadway is in a state of high stress. Under the condition of a 10 m wide protective pillar, the peak vertical stress and energy density are shifted from the pillar to roadway virgin coal region, with peak values of 9.5 MPa and 208.3 kJ/m3, respectively. The decrease in vertical stress and energy density improves the stability of the protective pillar, resulting in the roadway being in a state of low stress. Field monitoring suggested that the proposed 10 m protective pillar width can effectively control the large deformation of the surrounding rock and reduce coal bump risk. The novel numerical modeling approach and design principle of protective pillars presented in this paper can provide useful references for application in similar coal mines.